2011
DOI: 10.1093/jxb/err357
|View full text |Cite
|
Sign up to set email alerts
|

Vipp1: a very important protein in plastids?!

Abstract: As a key feature in oxygenic photosynthesis, thylakoid membranes play an essential role in the physiology of plants, algae, and cyanobacteria. Despite their importance in the process of oxygenic photosynthesis, their biogenesis has remained a mystery to the present day. A decade ago, vesicle-inducing protein in plastids 1 (Vipp1) was described to be involved in thylakoid membrane formation in chloroplasts and cyanobacteria. Most follow-up studies clearly linked Vipp1 to membranes and Vipp1 interactions as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
132
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(140 citation statements)
references
References 101 publications
5
132
1
Order By: Relevance
“…25), these protein structures will trivially co-sediment with membranes. The closely related phage shock protein A (PspA) of Escherichia coli has been demonstrated to bind to the negatively charged lipid phosphatidylglycerol (PG) 26 , and thus IM30 binding to the negatively charged PG appears to be likely 27 . Mainly based on analyses of IM30-depleted chloroplasts and cyanobacteria, diverse functions have been suggested for IM30.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…25), these protein structures will trivially co-sediment with membranes. The closely related phage shock protein A (PspA) of Escherichia coli has been demonstrated to bind to the negatively charged lipid phosphatidylglycerol (PG) 26 , and thus IM30 binding to the negatively charged PG appears to be likely 27 . Mainly based on analyses of IM30-depleted chloroplasts and cyanobacteria, diverse functions have been suggested for IM30.…”
mentioning
confidence: 99%
“…Consequently, the name 'vesicle-inducing protein in plastids 1' (Vipp1) has been suggested. However, further studies have indicated that IM30 is involved in maintaining the structure and stability of internal membranes in chloroplasts and cyanobacteria, similar to its bacterial homologue PspA, and thus has a more protective function 27,28 . In addition, IM30 has been found to enhance protein translocation via the chloroplast Tat pathway 29 and involvement in photosystem biogenesis has been suggested 21,[30][31][32] .…”
mentioning
confidence: 99%
“…IM30 does not exhibit membrane spanning helices, as is typical for a canonical transmembrane protein (2, 3), and thus, it appears to peripherally bind to the cytoplasmic surface of the inner envelope/cytoplasmic membrane and TMs (5, 13). In fact, IM30 appears to exist in equilibrium between a soluble and a membrane-attached form (5).Based on computational analyses, IM30 contains seven ␣-helices, which are interrupted by small random coil domains, and these ␣-helices are predicted to be involved in the formation of coiled-coil structures (5,6,14,15). Although the tertiary structure of IM30 is not yet resolved, it is clear that IM30 monomers interact and assemble into large oligomeric ring complexes with molecular masses exceeding 2 MDa (5, 14).…”
mentioning
confidence: 99%
“…Based on computational analyses, IM30 contains seven ␣-helices, which are interrupted by small random coil domains, and these ␣-helices are predicted to be involved in the formation of coiled-coil structures (5,6,14,15). Although the tertiary structure of IM30 is not yet resolved, it is clear that IM30 monomers interact and assemble into large oligomeric ring complexes with molecular masses exceeding 2 MDa (5, 14).…”
mentioning
confidence: 99%
See 1 more Smart Citation